Case Report: A case study on the relationship between obesity and estrus in female captive panda - Zhou, Qiang; Luo, Bo; Yang, Bo; Li, Desheng; Wei, Rongping; Xie, Chunyu; Yu, Jinhua; Meng, Xiangqian; Cheng, Jianbin; He, Ming; Yang, Liu (Frontiers in Veterinary Science, 2025)
This study investigated a case of abnormal estrus in a captive adult female giant panda (Ailuropoda melanoleuca) (X#, 130 kg) in 2024 to explore the possible relationship between overweight or obesity and estrus behavior in female giant pandas. Behavioral observations and urinary estrogen conjugate/creatinine (EC/CR) measurements revealed a significantly attenuated hormonal profile (peak EC/CR: 34.1 ng/mg vs. normal range 80–150 ng/mg) alongside muted receptivity (e.g., absent tail-lifting). Comparative analysis with historical cases of abnormal estrus (panda 2#: obesity-linked low EC/CR; panda 1#: normal EC/CR with behavioral anomalies) implicated obesity as a driver of reproductive impairment. And several actionable interventions were proposed: bamboo-based dietary reform, structured exercise protocols, and gut microbiota monitoring. This case underscores obesity as a modifiable risk factor in captive panda reproduction, urging integration of metabolic health into breeding management.